Plant-based diets and total and cause-specific mortality: a meta-analysis of prospective studies - Mo, Qiwang; Wu, Jizhongrong; Lu, Yi; Zhang, Xiao (Frontiers in Nutrition, 2025)
ObjectiveThe adherence to plant-based diets has been shown to positively impact longevity by reducing the incidence and severity of lifestyle-related diseases. Previous studies on the association of plant-based dietary pattern, as evaluated by plant-based dietary index (PDI), healthy plant-based dietary index (hPDI) and unhealthy plant-based dietary index (uPDI), with mortality risk have reported inconsistent results. We performed the present meta-analysis to summarize evidence on this association and to quantify the potential dose–response relationship based on all available cohort studies.MethodsA comprehensive literature search and systematic review of relevant articles up to October 2024 was performed in PubMed and Scopus. The summary risk estimates (RR) with 95% confidence interval (CI) for the highest versus the lowest category of PDIs, hPDIs and uPDIs were calculated. Dose–response meta-analysis was also performed for studies reporting categorical risk estimates for at least three quantitative levels of PDIs, hPDIs and uPDIs.ResultsA total of 11 eligible cohort studies (13 datasets) were eventually included in this meta-analysis. Participants in the highest quintile of both the PDI and hPDI had a significantly decreased risk of all-cause mortality (pooled HRPDI = 0.85; 95% CI: 0.80–0.90; pooled HRhPDI = 0.86; 95% CI: 0.81–0.92) compared to participants in the lowest quintile. In contrast, the highest uPDI was associated with an increased risk of mortality (pooled HRuPDI = 1.20; 95% CI: 1.11–1.31). Dose–response meta-analysis showed that there was a non-linear relationship between PDI or hPDI level and all-cause mortality (p = 0.001 and p < 0.001 for non-linearity, respectively). No evidence of a non-linear relationship was observed for uPDI (p = 0.596 for non-linearity).ConclusionGreater adherence to PDI or hPDI dietary pattern was associated with a lower risk of mortality, whereas uPDI dietary pattern was positively associated with mortality risk. Thus, promoting a plant-based dietary pattern may be a key strategy in improving public health and reducing the burden of diet-related mortality.